Tinjauan Yuridis terhadap Tindak Pidana Penipuan dengan Modus Sumbangan Fiktif di Media Sosial - Eprilia Atriya Nur Afifah; Vieta Imelda Cornelis; Moh. Taufik (JOURNAL OF SHARIA ECONOMICS, 2024)
Fraud using fictitious donations on social media is a phenomenon that is increasingly widespread in Indonesia. This method utilizes digital platforms to trick the public with emotional narratives and fake donation invitations. This article aims to analyze the juridical aspects of the criminal act of fictitious donation fraud, including the legal basis, law enforcement mechanisms, and protection for victims. The method used is a qualitative approach with literature study and case analysis. The research results show that perpetrators utilize false identities and misleading information to attract donations, while law enforcement faces challenges in terms of digital evidence and coordination between agencies. The proposed recommendations include increasing public digital literacy, strengthening regulations, and collaboration between social media platforms and law enforcement officials.